2018
DOI: 10.1590/rbz4720160391
|View full text |Cite
|
Sign up to set email alerts
|

Glycemic control in minks with tendency to obesity in the perinatal period with the use of HbA1C

Abstract: The objective of this study was to investigate the usefulness of HbA1C as a test in monitoring the long-term glycemic control during the perinatal period in minks with the tendency to obesity. On the scanbrown mink farm, screening research on one-year-old females showing predilections to obesity was conducted. In the first year of the experiment, 120 females were assessed using body condition score (BCS) system. The two groups that differed significantly in body weight were selected based on the BCS system and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 10 publications
0
2
0
Order By: Relevance
“…As a result of selection, new color varieties of mink have appeared over the recent years, and the body weight of farmed mink increased. According to Boudreau et al [2014] and Bis-Wencel et al [2018], selection for largest possible skins often leads to obesity and fatness in mink, and consequently to reproductive problems. Also, Tinggaard et al [2012] showed that females that were too obese gave birth to smaller litters than those in the normal body condition.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…As a result of selection, new color varieties of mink have appeared over the recent years, and the body weight of farmed mink increased. According to Boudreau et al [2014] and Bis-Wencel et al [2018], selection for largest possible skins often leads to obesity and fatness in mink, and consequently to reproductive problems. Also, Tinggaard et al [2012] showed that females that were too obese gave birth to smaller litters than those in the normal body condition.…”
Section: Discussionmentioning
confidence: 99%
“…Many authors express an opinion that the optimal body condtion is the key factor in terms of the reproductive success of the herd [Boudreau 2012, Boudreau et al 2014, Felska-Błaszczyk et al 2017, Bis-Wencel et al 2018, Felska-Błaszczyk and Seremak 2020. Well designed restrictive feeding regime using reduced energy feeds, followed by the flushing period preceeding the mating season, has a positive effect on the reproductive performace of both males and females [Tauson 1988, Tauson 1993.…”
Section: Introductionmentioning
confidence: 99%